Odpowiedź :
[tex]1) \ 5x-3=4x-4[/tex]
[tex]5x-4x=-4+3[/tex]
[tex]x = -1[/tex]
[tex]2) \ 2(x+4)=x-7[/tex]
[tex]2x+8=x-7[/tex]
[tex]2x-x=-7-8[/tex]
[tex]x = -15[/tex]
[tex]3) \ 9-x=(16+x)-(7+2x)[/tex]
[tex]9-x=16+x-7-2x[/tex]
[tex]-x - x + 2x = 16-7-9[/tex]
[tex]-2x+2x=9-9[/tex]
[tex]0=0[/tex]
[tex]4) \ \frac{x}{5} -\frac{x}{2} =2-\frac{x}{3} \ \ \ \ \ \ \ \ \ /*30[/tex]
[tex]6x-15x=60-10x[/tex]
[tex]6x-15x+10x=60[/tex]
[tex]-9x+10x=60[/tex]
[tex]x=60[/tex]
[tex]5) \ x-\frac{3x+1}{4} =\frac{1}{5} \ \ \ \ \ \ \ \ /*20[/tex]
[tex]20x-5(3x+1)=4[/tex]
[tex]20x-15x-5=4[/tex]
[tex]5x=4+5[/tex]
[tex]5x=9 \ \ \ \ \ \ \ \ /:5[/tex]
[tex]x=\frac{9}{5} =1\frac{4}{5}[/tex]
[tex]6) \ 7x-x(x-5)+(x^2-6)=5(x+6)-x(x-7)[/tex]
[tex]7x-x^2+5x+x^2-6=5x+30-x^2+7x[/tex]
[tex]7x-x^2+5x+x^2-5x+x^2-7x=30+6[/tex]
[tex]7x+5x-5x-7x+x^2=36[/tex]
[tex]x^2=36 \ \ \ \ \ \ \ \ \ /\sqrt{ \ \ }[/tex]
[tex]x=\sqrt{36} =6[/tex]